The Double Comfort Safari Club - McCall Smith, Alexander, 1948- (New York : Anchor Books, Random House, 2010)
Mma Ramotswe and Mma Makutsi travel to the north of Botswana, to the stunning Okavango Delta, to visit a safari lodge where there have been several unexplained and troubling events--including the demise of one of the guests
Keywords: No. 1 Ladies' Detective Agency (Imaginary organization) -- Fiction; Ramotswe, Precious (Fictitious character) -- Fiction; Women private investigators -- Fiction; Okavango River Delta Region (Botswana) -- Fiction